Role of corticosteroid therapy in IgA nephropathy; where do we stand? - Shankar Prasad Nagaraju; Sindhura Lakshmi Koulmane Laxminarayana; Aswani Srinivas Mareddy; Srikanth Prasad; Sindhu Kaza; Srinivas Shenoy; Karan Saraf; Dharshan Rangaswamy; Ravindra Prabhu Attur; Rajeevalochana Parthasarathy; Uday Venkat Mateti; Vasudeva Guddattu; et al. (Journal of Nephropathology, 2017)
Background: Current KDIGO guidelines suggest corticosteroids (CS) administration in IgA nephropathy (IgAN) with persistent proteinuria >1 g/d despite 3-6 months of supportive care and estimated glomerular filtration rate (eGFR) >50 mL/min/1.73 m2 . The benefits of CS in patients with eGFR <50 mL/min/1.73 m2 is unclear. Objectives: To assess the effect of steroids on disease progression and proteinuria in IgAN patients with eGFR < 50 mL/min/ 1.73m2 compared with >50 mL/min/1.73 m2 . Patients and Methods: A cohort of biopsy proven primary IgAN diagnosed between March 2010 - February 2015 who received oral CS with minimum follow-up of 6 months were included. They were categorized into two groups according to their eGFR (group 1 - eGFR <50 mL/min/1.73 m2 , group 2 - eGFR >50 mL/min/1.73 m2 ). The eGFR and urine protein creatinine ratio (UPCR) were followed up at entry, 6 months, 12 months and at the end of follow-up. Outcomes studied were change in eGFR, proteinuria and progression to end-stage renal disease (ESRD). Results: Out of 44 patients, 23 were in group1 and 21 patients in group 2. At the end of follow-up, similar reduction of proteinuria (UPCR) was observed in both groups (P=0.62). However, group 1 had a significant fall in eGFR compared to improvement in group 2 (P=0.004). One in each group has reached CKD stage 5 (P=0.73). Conclusions: Addition of CS to conservative treatment in IgAN patients with initial eGFR<50 ml/min/1.73 m2 seems to reduce proteinuria but not beneficial in preventing progression of disease as compared to patients with higher eGFR (>50 mL/min/1.73 m2 ).